2020
DOI: 10.1126/science.aay9189
|View full text |Cite
|
Sign up to set email alerts
|

The human tumor microbiome is composed of tumor type–specific intracellular bacteria

Abstract: Bacteria were first detected in human tumors more than 100 years ago, but the characterization of the tumor microbiome has remained challenging because of its low biomass. We undertook a comprehensive analysis of the tumor microbiome, studying 1526 tumors and their adjacent normal tissues across seven cancer types, including breast, lung, ovary, pancreas, melanoma, bone, and brain tumors. We found that each tumor type has a distinct microbiome composition and that breast cancer has a particularly rich and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
1,419
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 1,431 publications
(1,631 citation statements)
references
References 75 publications
55
1,419
5
3
Order By: Relevance
“…Moreover, the sarcoma TME may contain a specific microbiome (Nejman et al , 2020): A recent study described that bacterial DNA can be found in most CHSs. Bacteria were mostly intracellular and were detectable in immune and tumor cells (Nejman et al , 2020).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the sarcoma TME may contain a specific microbiome (Nejman et al , 2020): A recent study described that bacterial DNA can be found in most CHSs. Bacteria were mostly intracellular and were detectable in immune and tumor cells (Nejman et al , 2020).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…Moreover, the sarcoma TME may contain a specific microbiome (Nejman et al , 2020): A recent study described that bacterial DNA can be found in most CHSs. Bacteria were mostly intracellular and were detectable in immune and tumor cells (Nejman et al , 2020). Interestingly, metabolic functions related to intratumoral bacteria appeared tumor type‐specific; that is, degradation of hydroxyprolines by bacteria was enriched in CHSs (Nejman et al , 2020).…”
Section: Epidemiology Of Sarcomamentioning
confidence: 99%
“…A recent comprehensive investigation of microbiomes across seven cancer types (not yet including ESCC) indicates that intracellular bacteria are widespread in tumors [39]. Particularly, 19 prevalent bacteria are characterized [39], including genera of streptococcus and fusobacterium, which are found in our ESCC microbiota. It is not clear whether the enriched bacterial species or genera identi ed in our study can reside in ESCC to facilitate the microenvironment to boost cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…Treponema amylovorum is a subgingival plaque bacteria species involved in chronic periodontitis [37]. Streptococcus infantis is a part of the salivary microbiome [38]and a prevalent bacteria in breast cancer [39]. Aggregatibacter segnis is an oral bacterial species in oral cancer [40].…”
Section: Discussionmentioning
confidence: 99%
“…The integrated analysis with the three models allows us to present a relatively complete and reliable 'picture' of the process (mechanism) underlying the tissue microbiome distribution and dispersal patterns. In perspective, our study, if successful, is likely to offer important insights for investigating the relationship between breast tumor development and breast tissue microbiomes (Nejman et al 2020;Poore et al 2020). Urbaniak et al (2016) collected samples from women following lumpectomies or mastectomies and from healthy individuals.…”
Section: Introductionmentioning
confidence: 99%